(untitled) (Research, Society and Development, 2022)
Introduction: Tuberculosis is an infectious disease that spreads through the air. It is known that the world is experiencing a major epidemic caused by M. tuberculosis, within this context, the disease becomes a serious problem for public health. Methodology: The present epidemiological profile developed is a cross-sectional study, retroactive to the year 2021, quantitative with statistical numbers and qualitatively discussed in the course of the work, in which the researchers deal with public data collected and saved in the DataSUS program. Results: during this section, the qualitative-quantitative methodology was addressed based on the following variables: “types of entry”, “Clinical outcome of the infection”, “Sputum culture”, “Coinfection with HIV/AIDS”, “Rapid TB test and sensitivity to antibiotic therapy", "1st sputum smear sample", "clinical form of infection", "Confirmation of infection by laboratory examination", "Age groups of patients", "Region of residence", "Gender of affected by tuberculosis in 2021”. Final considerations: The wide vaccination coverage of the vaccines already available, the elaboration of public policies aimed at tuberculosis control, as well as the creation of new strategies to combat the disease can contribute to reduce the new annual tuberculosis cases.